Combined high-speed holographic shape and full-field displacement measurements of tympanic membrane - Razavi, Payam; Tang, Haimi; Rosowski, John J.; Furlong, Cosme; Cheng, Jeffrey T. (Journal of biomedical optics, 2019)
The conical shape of the tympanic membrane (TM or eardrum) plays an important role in its function, such that variations in shape alter the acoustically induced motions of the TM. We present a method that precisely determines both shape and acoustically induced transient response of the entire TM using the same optics and maintaining the same coordinate system, where the TM transient displacements due to a broadband acoustic click excitation (50-μs impulse) and the shape are consecutively measured within <200  ms. Interferograms gathered with continuous high-speed (>2  kHz) optical phase sampling during a single 100-ms wavelength tuning ramp allow precise and rapid reconstructions of the TM shape at varied resolutions (50 to 200  μm). This rapid acquisition of full-field displacements and shape is immune to slow disturbances introduced by breathing or heartbeat of live subjects. Knowledge of TM shape and displacements enables the estimation of surface normal displacements regardless of the orientation of the TM within the measurement system. The proposed method helps better define TM mechanics and provides TM structure and function information useful for the diagnosis of ear disease.